2017
DOI: 10.1002/tesj.333
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐Mediated Tasks: Affordances Considered From the Learners’ Perspectives

Abstract: Within the field of instructed second language acquisition, there has been an increase in the amount of research reporting on task‐based language teaching (TBLT; Kim, ; Van den Branden, ). The pervasive use of technology has prompted researchers to examine the potential synergies between TBLT and technology‐mediated teaching (González‐Lloret & Ortega, ; Ziegler, ). The present study examines the perception of 20 learners of English as a second language toward the use of tasks across two modes: a traditional pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Research on pedagogical implications has proposed the benefits of incorporating technology into traditional paper-and-pencil-based classrooms, but further studies are needed. Payant and Bright's (2017) findings also show that although most participants prefer the technology-mediated tasks, five participants articulated a preference for paper-mediated tasks. In fact, some participants reported very negative views toward using computers.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Research on pedagogical implications has proposed the benefits of incorporating technology into traditional paper-and-pencil-based classrooms, but further studies are needed. Payant and Bright's (2017) findings also show that although most participants prefer the technology-mediated tasks, five participants articulated a preference for paper-mediated tasks. In fact, some participants reported very negative views toward using computers.…”
Section: Introductionmentioning
confidence: 65%
“…Their study compared students' perceptions of technologymediated TBLT and traditional paper-and-pencil tasks. Payant and Bright (2017) found that learners preferred the weak form of technology-mediated TBLT over the task and most saw benefits of doing the technology-based TBLT task, regardless of preference, including developing keyboarding performances and searching performances. Payant and Bright (2017) suggested that using a technology-mediated task and developing computerrelated performances may result in different language performances (i.e., skimming and scanning).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…L'analyse des constats des apprenants suggère que parmi les différents types de tâches, celle-ci ne poussait pas assez les apprenants et qu'elle les encadrait trop. Dans une étude récente, nous avons examiné les synergies entre les tâches et la technologie (Payant et Bright, 2017). Dans cette étude, les apprenants devaient accomplir une tâche de type échange d'informations.…”
Section: Discussionunclassified